ALKALI ELEMENTS (Na, K, Rb) AND ALKALINE EARTH ELEMENTS (Mg, Ca, Sr, Ba) IN THE ANOXIC BRINE OF ORCA BASIN, NORTHERN GULF OF MEXICO - Schijf J. (My University, 2007)
A profile of filtered seawater and brine samples was collected in the summer of 2003 from a depth of 1500 m down to the bottom of the anoxic, hypersaline Orca Basin (northern Gulf of Mexico). Using ion chromatography and inductively coupled plasma mass spectrometry (ICP-MS), these samples were analyzed for alkali cations (Na+, K+, Rb+), alkaline earth cations (Mg2+, Ca2+, Sr2+, Ba2+), and the major anions chloride (Cl-) and sulfate (SO42-). Major ion concentrations in the brine are consistent with previous studies, confirming that Na plus Cl make up more than 95% of its composition, hence governing its density and hydrodynamic stability. Binary mixing plots across the interface between deep Gulf of Mexico seawater and the anoxic brine are generally linear, but display substantial deviations from conservative behavior at the steepest part of the pycnocline for all analytes except Na, Cl, and Ca. Negative deviations signify localized cation removal by an adsorption or ion-exchange process, probably associated with the dense layers of particles that are trapped there. Especially strong Mg removal may be indicative of dolomitization, whereby the concomitant release of Ca counters its adsorption, resulting in zero net Ca removal. A positive deviation for sulfate is attributed to bacterial sulfide oxidation. Concentrations of Rb, Sr, and Ba in the homogeneous brine, reported here for the first time, are enriched by factors of 1.5, 1.4, and ~ 9, respectively, with respect to the overlying seawater. Unlike Ca and Sr, Ba concentrations in the brine are clearly controlled by the solubility of its sulfate salt (barite), causing a maximum of 670 nmol/kg at the interface. Several independent lines of evidence suggest that the brine is formed outside the basin, most likely by the interaction of seawater with regionally extensive evaporite deposits. A simple mass balance shows that the dissolution of about 280 g of halite per kg of seawater can account for the extreme concentrations of Na and Cl in the Orca Basin brine. The same mass balance was applied to a number of minor constituents (K, Rb, Mg, Ca, Sr, SO4, Br, total iodine) in order to calculate what abundances in the halite are required to reproduce their concentrations in the brine as measured in the present work and by others. The results are entirely compatible with the composition of the Jurassic Louann Salt, specifically with the median of compositions published for a transect spanning early to late stage halites. Elevated abundances of K and Rb point to contributions from bittern facies modified by prior diagenetic contact with seawater. © 2007 Elsevier B.V. All rights reserved.
Keywords: ALKALI ELEMENTS; ALKALINE EARTH ELEMENTS; ANOXIC; EVAPORITE; HYPERSALINE; ORCA BASIN; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская